Manusia Sebagai Khalifatullah : Kajian Filosofis dalam Perspektif al-Qur`an - Ali Mu`tafi (Pusdikra-Publishing.com, 2021)
The article aims to reveal humans as khalifatullah: a philosophical study from the perspective of the Koran. This is important to do to provide a reference for how humans can think and act based on the tasks attached to them. This research is library research with a philosophical approach. The results of the research show that philosophically the Qur'an examines humans including discussing the purpose of life, position and duties of humans. Everything is related to human ontological thinking. Therefore, it is always inseparable from the Islamic perspective regarding the purpose of his life to worship, his position as a regulator and conservator of the earth, with his duties and functions as a servant of Allah, and as Allah's representative, substitute and successor to the species that preceded him, inheriting the earth as a form of Allah's trust that must be fulfilled. keep. So humans are leaders of themselves, their families and society, and based on this trust, humans are held accountable for the mandates they have received. The implication of the research is that narrative understanding brings synergistic philosophical understanding to the Muslim person so that he becomes a perfect Muslim. This research is expected to contribute to the philosophy of Islamic education.